Effect of research and development expenditure on the financial sustainability of Standard and Poor listed firms - Hamid Ghazi H Sulimany (Humanities & Social Sciences Communications)
Abstract This study assesses the effect of research and development expenditure on the financial sustainability of companies listed on the Standard and Poor 500 listed firms. The panel data of 231 companies from 2015 to 2022 are analysed using the fixed effects approach. Further evidence is also provided using the generalised method of moments framework. The results support signalling theory, suggesting that research and development expenditure may enhance a firm’s reputation and help it to gain a competitive advantage, resulting in greater profitability and consistent value creation. This finding implies that companies can achieve sustainable performance by investing in research and development. Policymakers and regulators should provide incentives to companies to pay more attention to research and development investments. Such investments may promote innovation, enhance the competitive advantage, and boost the revenue generation of companies, thus enabling sustainable performance.